(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2023)
The article begins with a brief overview of the theoretical foundations of STEAM education, to be followed It then provides a critical overview of different curricula, pedagogies, and technologies used in preschool education around the world. The article also examines the experience of STEAM technologies in preschool education in foreign countries and Uzbekistan.